GENETIC DIVERSITY OF Hymenaea courbaril L. IN THE MATO GROSSO AMAZON: IMPLICATIONS FOR CONSERVATION - Rocha, Vinicius Delgado da; Bispo, Rosimeire Barboza; Pedri, Eliane Cristina Moreno de; Cardoso, Elisa dos Santos; Zortéa, Kelli Évelin Müller; Rossi, Ana Aparecida Bandini (Floresta, 2019)
Hymenaea courbaril L. (Fabaceae) is a tree species popularly known as 'jatobá'. Its wood is largely sold and its fruits are used as a food and medicinal resources. This species has been subjected to logging and habitat destruction. The knowledge about genetic polymorphism is important for the conservation of species affected by anthropic action. In this study, we analyzed the genetic diversity of natural populations of Hymenaea courbaril in the Mato Grosso Amazon. Seven microsatellite primers were used to genotyping of 43 individuals distributed in five populations in the north region of Mato Grosso State. All the seven primers were polymorphic, with 72 alleles detected, averaging 10.29 per locus. Expected and observed heterozygosities averaged 0.85 and 0.29 per locus, respectively. The fixation index was positive for all populations, suggesting excess homozygotes, probably due to inbreeding. Molecular analysis of variance revealed that 85.33% of genetic diversity is within the populations. Based on the UPGMA dendrogram, the individuals were divided into six groups. In the clustering provided by Structure software, four groups were formed which did not correspond to the geographic distribution of the individuals, indicating that the populations are not geographically structured. All sampled populations present elevated levels of genetic diversity, and so they can be used for conservation projects. Genetic variation is higher within the analyzed populations; therefore, several individuals must be conserved per population.